Analysis of current overflow disturbance towards neutral grounding resistance condition - Yusniati, Y; Hernawati, Tri; Parinduri, Luthfi; Krianto Sulaiman, Oris; Suliawati, S (International Journal of Engineering and Technology, 2018)
The power transformer at the substation serves to deliver power from high voltage to low voltage or vice versa. In the transformer section, there is a neutral grounding resistance mounted serially with the secondary neutral on the transformer before connecting to the ground that serves to minimize the fault current. One of the disadvantages of the NGR grounding system is when there is a short-circuit one-phase interruption to the ground, the soil disturbance current may be larger than the limit of the NGR value that used. This can cause damage to NGR and other equipment. This study discusses about current overflow disturbance in NGR at State Electricity Company or PLN, PLN Lamhotma Substation application in normal condition with cable channel length 28,215,244 feet and at 20 kV voltage of ground capacitance with manual calculation obtained Ico = 1,16 A and if there is a one-phase disturbance to the ground then the greater the current will be Ig = 4.61A. To prevent the enlargement ofthis one phase short circuit current, then it is measured towards neutral grounding resistance.Â Â